Glycemic index and sensory evaluation of breadfruit resistant starch bread - Zarinah, Zakaria; Syamimi, Yusuf; Norshazila, Shahidan; Nurul Zaizuliana, Rois Anwar (2018)
The objective of the present study is to determine the Glycaemic Index (GI), mood effect and cognitive function of chocolate fortified with purple sweet potato (PSP), orange sweet potato (OSP) and pumpkin among female students. The control and three types of fortified chocolates were tested on 10 healthy female students to determine their blood glucose level before (0 min) and after 30, 60, 90 and 120 min of chocolate consumptions and the GI of these chocolate was determined. These fortified chocolates were also tested on another 30 healthy female students to observe mood effect for every 30 until 90 min by using a 7-scale mood questionnaire while the percentage of items memorised (any order and in order) after 30 minutes of chocolate consumption was used to observe their cognitive function. From the results, this study concluded that chocolates fortified with PSP and pumpkin were classified as low GI food while chocolates fortified with OSP were medium GI food. Moreover, the consumption of these fortified chocolates also showed good effect on mood and cognitive function.